Design of all-optical graphene switches based on a Mach-Zehnder interferometer employing optical Kerr effect - Armaghani, Sahar; Khani, Shiva; Danaie, Mohammad (Superlattices and microstructures, 2019)
In this paper, all-optical switches using a novel combination of graphene and insulator-metal plasmonic waveguides are proposed. For the proposed switches the optical Kerr effect is used to change the chemical potential of graphene-based plasmonic waveguides which are located in arms of a Mach-Zehnder interferometer. The phase mismatch induced due to the chemical potential variation triggers the switching mechanism. Three dimensional finite difference time domain (FDTD) method has been used for numerical investigation of the designed graphene switches. Silver is the metal used for the design of the Mach-Zehnder interferometer and GaAs is chosen as the Kerr material. The proposed all-optical switches can be used for highly integrated optical circuits and for all-optical signal processing. •Two novel graphene-based all-optical plasmonic switches are designed in this paper.•The switching topologies are based on graphene and insulator-metal plasmonic structures.•Kerr effect results in chemical potential variation of graphene waveguides used in a Mach-Zehnder interferometer (MZI).•The phase mismatch obtained due to chemical potential variation between the arms of the MZI is the switching basis.